Profiling of The Lemongrass Oil Aroma and Their Structure-Odor Relationship: In Silico Study - Udrika Lailatul Qodri; Edi Priyo Utomo; Elvina Dhiaul Iftitah (Chemistry Department, The University of Brawijaya, 2017)
Structure-odor relationship (SOR) has previously studied by semantic numerically in different Fragrance. We hypothesise that in silico method such as molecular dynamics, together with docking of the interaction between human olfactory receptor (OR1G1) and ligands, can offer extremely valuable tools of modelling SOR. Hence, the present study was carried out to express the SOR of citronellal oil fraction compare with reference smelling of floral, musk, green, wood, and fruit by employing docking and multiple discriminant analysis (MDA). Our study reveals that the number dissociation constant (Kd), bond distance, HOMO-LUMO (AE), dipole moment, kind of amino acids, Log P, surface area and hydropathy as the variable SOR from in silico anaysis. Our result has shown ligands and OR1G1 interacted with Van Der Waals and electrostatic model. MDA analysis shown molecule reference floral and fraction of lemongrass oil have similar correlation based on variable SOR with linier regression of all variable SOR to Kd value for every reference odor is R2 = 1.